Diterpenes from the berries of Juniperus excelsa - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
From the hexane extract of berries of Juniperus excelsa, one new and four known diterpenes were isolated besides a known sesquiterpene. The structures of the known diterpenes were identified as isopimaric, isocommunic, (-)ent-trans communic and sandracopimaric acids, along with the sesquiterpene 4a-hydroxycedrol and the new compound which was elucidated as 3 alpha-acetoxylabda-8(17), 13(16), 14-trien-19-oic acid (juniperexcelsic acid). Cytotoxic activity of the hexane extract was investigated against a panel of cell line and found highyl active against LNCaP, KB-V (+VLB) and KB-V (-VLB) cell lines. Furthermore, the hexane and methanol extracts, and the new compound were found to be moderately active against Mycobacterium tuberculosis. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: Juniperus excelsa; Cupressaceae; berries; diterpenes; juniperexcelsic acid; sesquiterpene; cytotoxic; antituberculosis and antibacterial activity